2014
DOI: 10.1063/1.4885351
|View full text |Cite
|
Sign up to set email alerts
|

The gas-liquid surface tension of argon: A reconciliation between experiment and simulation

Abstract: We present a simulation of the liquid-vapor interface of argon with explicit inclusion of the three-body interactions. The three-body contributions to the surface tension are calculated using the Kirkwood-Buff approach. Monte Carlo calculations of the long-range corrections to the three-body contribution are calculated from the radial distribution function g((2))(z1, cos θ12, r12). Whereas the effective two-body potentials overestimate the surface tension by more than 15%, the inclusion of the three-body poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 43 publications
6
41
1
Order By: Relevance
“…The results presented by Goujon et al 1 do not support that claim because of two reasons: First, their simulation data exhibit large systematic deviations to other sources which puts doubt on their simulation methodology. Second, they have exclusively focused on the three-body interaction, neglecting other features of the molecular interactions.…”
contrasting
confidence: 46%
“…The results presented by Goujon et al 1 do not support that claim because of two reasons: First, their simulation data exhibit large systematic deviations to other sources which puts doubt on their simulation methodology. Second, they have exclusively focused on the three-body interaction, neglecting other features of the molecular interactions.…”
contrasting
confidence: 46%
“…40 This is consistent with a previous study by Goujon et al, where the asymptotic behavior can be observed with a r vdw of 1.8 nm for Ar, which was modeled with a σ of 0.339 52 nm. 37 Thus, we anticipate a r vdw of 5σ might be sufficient also for other systems. However, for model potentials that do not use the standard Lennard-Jones term, the definition of σ might be ambiguous.…”
Section: Resultsmentioning
confidence: 99%
“…The dependence of surface tension on r vdw has been reported in the past. [36][37][38] The analysis of the previous data shows that similar linear dependence of γ to (1/r vdw ) 2 can also be observed in methane 36 T c estimated using all the choices of r vdw are reported to provide more data points. From this figure, it is clear that the box size has much smaller influence on T c than r vdw .…”
Section: Computational Details Of the Direct Interface Simulationsmentioning
confidence: 93%
“…The data for simulations without the LRC to the energy are taken from our previous work. 1 Looking at the results for the LJ potential, we see that the expected deviations from experiment vanish, when the long range corrections are included in the simulation. The saturated liquid density and the vapor pressure are affected by the long range correction and the results with the long-range correction are much closer to experiment, giving relative deviations of less than 0.5% for liquid density and less than 5% for vapor pressure.…”
mentioning
confidence: 99%
“…In a recent article, 1 we calculated the vapor-liquid equilibrium (VLE) properties of argon using direct Monte Carlo simulations of the liquid-vapor interface. We have shown that both the VLE properties and the surface tension can be calculated accurately when considering a real twobody potential coupled with an explicit three-body term.…”
mentioning
confidence: 99%